2019
DOI: 10.3847/1538-4357/aaf395
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Core-collapse Progenitor Mass Distribution of the Small Magellanic Cloud

Abstract: The physics of core-collapse (CC) supernovae (SNe) and how the explosions depend on progenitor properties are central questions in astronomy. For only a handful of SNe, the progenitor star has been identified in preexplosion images. Supernova remnants (SNRs), which are observed long after the original SN event, provide a unique opportunity to increase the number of progenitor measurements. Here, we systematically examine the stellar populations in the vicinities of 23 known SNRs in the Small Magellanic Cloud (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 274 publications
(516 reference statements)
6
33
0
1
Order By: Relevance
“…Same as Figure 2 but for primary (s1; upper left panel), secondary (s2; upper right panel) and tertiary (s3; bottom panel) LC symmetry.M ej are within typical ranges for stars massive enough to experience a SN, and in agreement with observations of SN progenitor stars in pre-explosion images and supernova remnants (M ej 8-25 M )(Smartt 2009;Morozova et al 2018;Auchettl et al 2019). Higher-mass progenitors cannot be excluded given observations of stars as massive as > 150 M in the Milky Way galaxy(Crowther et al 2010).…”
supporting
confidence: 86%
“…Same as Figure 2 but for primary (s1; upper left panel), secondary (s2; upper right panel) and tertiary (s3; bottom panel) LC symmetry.M ej are within typical ranges for stars massive enough to experience a SN, and in agreement with observations of SN progenitor stars in pre-explosion images and supernova remnants (M ej 8-25 M )(Smartt 2009;Morozova et al 2018;Auchettl et al 2019). Higher-mass progenitors cannot be excluded given observations of stars as massive as > 150 M in the Milky Way galaxy(Crowther et al 2010).…”
supporting
confidence: 86%
“…Ne and Mg are also higher than solar in J0047−7308, while its high absorption (N H = 1.4 ± 0.2 × 10 22 cm −2 ) prevents a meaningful measurement of its oxygen abundance. Finally, we note that the large variation of N H between these three objects indicates that even though close in projected position, they might be at different distances and not associated to the same star-forming event/region, as implicitly assumed in Auchettl et al (2019).…”
Section: Notes On Individual Smc Snrsmentioning
confidence: 58%
“…MCSNR J0041-7336 (DEM S5) is far off to the south-west of the main SMC Bar and thus has the lowest recent star formation of the whole sample, but a PWN candidate was recently identified in it, strongly suggesting a CC SN origin. This explains the discrepancy with Auchettl et al (2019) who list only one type Ia candidate SNR, but whose CC SNR classification is based on the projected star-formation history alone. Given the significant extent/depth of the SMC, such an interpretation is not warranted.…”
Section: The Ratio Of CC To Type Ia Sne In the Smcmentioning
confidence: 84%
“…Apart from distinct turnoffs in intermediate ages, we also noted the existence of a distinct turnoff around 56-120Myr old. Enhanced SF for this period was also reported by Harris and Zaritsky [2004], Rubele et al [2015] and Auchettl et al [2019] who showed that a large fraction of the supernova remnants in the SMC indicated a burst of star formation between 50 and 200 Myr ago. We have investigated the kinematic behaviour of this population using proper motion measurements from Gaia DR2.…”
Section: Introductionsupporting
confidence: 80%